PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT HARMONI MITRA UTAMA BANJARMASIN - Mailiana Mailiana; Diana Hayati (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
Abstract, This study aims to examine the effect of work motivation on the performance of employees of PT Harmoni Mitra Utama Banjarmasin because it is suspected that work motivation affects the performance of employees of PT Harmoni Mitra Utama Banjarmasin. The method used in this study is a quantitative analytical method, which provides empirical evidence of the effect of work motivation as an independent variable with employee performance as the dependent variable at PT Harmoni Mitra Utama. While the subjects in this study were all employees, namely 45 respondents. The results of this study are the results of the SPSS output from simple linear regression proving that the variables of Physiological Needs (X1), Safety Needs (Security) (X2), Social Needs (X3), Appreciation Needs (X4) and Self-Actualization (X5) simultaneously affect the performance of employees (Y) at PT Harmoni Mitra Utama.